MOLECULAR IDENTIFICATION AND LOCAL ISOLATE BACTERIAL ACTIVITY TEST AS BIOCONTROL CANDIDATES TO TACKLE Vibrio Spp INFECTIONS AT VANNAMEI SHRIMP CULTIVATION (Litopenaeus vannamei) IN EAST LAMPUNG - Heidy Riana; Supono Supono; Agus Setyawan (e-Jurnal Rekayasa dan Teknologi Budidaya Perairan, 2021)
Pacific white shrimp (Litopenaeus vannamei) is a widely cultivated type of shrimp with high economic value. One of the obstacles in pacific white shrimp cultivation is an infectious disease, especially Vibrio spp. This study aims to identify bacteria of biocontrol candidate against Vibrio spp. This research was conducted by the Laboratory of Fisheries and Marine, Faculty of Agriculture, University of Lampung and the laboratory of PT. Indolab Utama, West Jakarta, from September 2019 to January 2020. Bacteria of Biocontrol candidate were isolated from traditional shrimp pond water in Purworejo Village, Pasir Sakti District, East Lampung Regency. Water samples were taken from the inlet, plot, and outlet. The bacterial screening was carried out by testing the antagonism of bacterial isolates isolated from water samples with several Vibrio bacteria, namely V. harveyi, V. algynoliticus, and V. parahemolyticus on Sea Water Complete (SWC) medium. The bacterial isolates with the highest inhibitory activity were then identified morphologically, biochemically, and molecularly by 16s rRNA. The results showed that from those 10 isolates was found 1 bacterial isolate from water samples. Only one pond plot isolate (P1) was found that had inhibitory activity against V. harveyi and the size was 21 mm. The morphological test results showed the colonies were round, flat edges, convex elevation, cream colored, and included in the negative gram bacteria group. The results of biochemical tests showed that the bacteria were motile. Meanwhile, the molecular test results with 16s rRNA showed that the P1 bacteria were 99% similar to Aeromonas caviae isolates, which were found potential as biocontrol candidates because they can inhibit the growth of V. harveyi bacteria, which was characterized by the formation of a clear zone around the paper disk.